Friction and wear characteristics of electrodeposited nanocrystalline nickel-tungsten alloy films - Haseeb, A.S. Md. Abdul; Albers, U.; Bade, Klaus (Elsevier, 2008)
Electrodeposited nanocrystalline nickel-tungsten alloys are being investigated as an attractive alternative to electrodeposited nickel for applications involving fabrication of micro electro mechanical systems (MEMS). Ni-W alloys are also being considered as an environmentally friendly alternative to hard chrome plating in some cases. In applications involving sliding contacts such as in micro-gears in MEMS, mould inserts, etc., tribological properties of Ni-W alloys would be of relevance. In this work, the sliding friction and wear characteristics of Ni-W alloys with different tungsten contents were investigated and compared with that of nickel film deposited from sulphamate bath commonly used in microfabrication. For wear tests, Ni-W alloy films of about 5-7 mu m, deposited from ammonia-citrate baths on copper substrates were employed. The alloy films possessed W contents in the range of 8.4-12.7 at. and had an average grain size of about 20 nm. Wear tests were conducted in a pin-on-disc type tribometer under un-lubricated conditions. All the wear tests were carried out at room temperature in air with a controlled relative humidity of 50 +/- 5 at a normal load and linear sliding speed of 1 N and 3 cm s(-1), respectively. Hardened steel balls were used as the counter body. Friction force was recorded online during the wear test. Wear damage on Ni and Ni-W alloy films was estimated from the width of the wear track and the wear rate of the counter body was calculated from the worn volume. Results show that Ni-W alloys have somewhat lower friction coefficient against steel counter body as compared with that of the nickel-steel pair. Addition of tungsten to nickel is also seen to result in an improvement in wear resistance. Friction and wear mechanisms operative in Ni-W alloys sliding against steel are discussed. (C) 2007 Elsevier B.V. All rights reserved.